Effect of the Thermomechanical Treatment on Corrosion Resistance of API 5L X70 Pipeline Steel - Mohamed M. Salem; Hesham Mraied; Adel M. Burakhis; Ibrahim K. Husain (African Journal of Advanced Pure and Applied Sciences, 2024)
The final microstructure and subsequent properties of state of the art HSLA pipeline steel plates are highly dependent on both the controlled rolling conditions and accelerated cooling conditions. This work utilized a novel physical deformation simulator to evaluate the evolution of microstructure in an API 5L X-70 steel during finish hot deformation and cooling. A series of plane strain compression (PSC) tests have been conducted to simulate the processes of plate rolling. The corrosion behaviour of received samples processed by TMCP was examined by potentiodynamic polarisation and electrochemical impedance spectroscopy tests. Electrochemical tests show corrosion resistance improvement due to microstructure refinement in selected TMCP process parameters.